The Impact Of Organizational Commitment On The Membership Growth In FGBMFI Chapter In East Java Region 1 In Surabaya - Aditia Djaja Tjiptobusono (Theological Journal Kerugma, 2021)
The title of The Impact of Organizational Commitment on The Membership Growth in FGBMFI Chapter in East Java Region 1 in Surabaya, was chosen by the author in this research study. The author wants to know whether the organizational commitment can increase the membership growth, especially in FGBMFI Chapter in East Java Region 1 in Surabaya. Pearson correlation coefficient and regression analysis, t-test and analysis of variance are used as the methods of analysis in this matter. Descriptive analysis was conducted to analyze the growth rate of members in FGBMFI Chapter in East Java Region 1 in Surabaya according to demographic groups. It turns out that organizational commitment has an influence, which is 39.4%, on the member growth in FGBMFI Chapter in East Java Region 1 in Surabaya.